Pengaruh Tegakan Mahoni (Swietenia macrophylla King) Terhadap Pertumbuhan dan Produksi Jarak Pagar (Jatropha curcas Linn.) - Nurheni Wijayanto; Anindita Kusumaningrum (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
The Influence of the Mahogany Stands (Swietenia macrophylla King.) On The Growth and Production of Jatropha curcas (Jatropha curcas Linn.)Agroforestry of mahogany and jatropha in Babakan Madang RPH was established. Jatropha were planted under mahogany stands of 3 years old (young mahogany stands), and 17 years (old mahogany stands). The difference of ages of mahogany may give influence on the growth and production of jatropha. The purpose of this research was to determine the influence of the mahogany stands (S. macrophylla) on the growth and seed production of Jatropha (J. curcas).The growth parameters of jatropha consisting of height, diameter, length, width tree crown were measured. These growth parameters were used to determine the tree crown width, as well as root length. Jatropha curcas plant height measurement was done by using graft-scale, while for measuring the widht, length and width of the crown, band meter was used. In this case, census method was applied. In every mahogany stand, 15 J. curcas trees were chosen for sampling. Root length of jatropha was measured by digging method. Horizontal and vertical roots were measured. The result showed that the growth of jatropha was significantly affected by the stand age of mahogany. Young mahogany stands produced better effect on height, diameter, length, width, and crown width of Jatropha than in old mahogany stnads. It was also strengthen by the results of the t-test (p